EFEK EKSTRAK TANAMAN ASHITABA PADA KADAR SERUM ALKALIN FOSFATASE (ALP) PADA TIKUS YANG TERPAPAR LUKA BAKAR - Johan, Andrew; Kusmiyati Tjahjono; Wenda Yoanda; Dwi Ngestiningsih; Lusiana Batubara (Universitas Imelda Medan, 2021)
Serum alkaline phosphatase (ALP) levels increases in burn tissue damage. Several bioactive compounds found in Ashitaba, are expected to reduce serum ALP levels and enhance the process of wound healing. This study aims to prove that administration of oral Ashitaba extract can reduce serum ALP levels in rats exposed to burn trauma. This study uses true experimental post-test control group design with a total of 20 Sprague dawley rats as samples. All samples were inflicted with 2nd degree burn wound and divided into 2 groups, treatment group (Ashitaba extract 300 mg/KgBW) and control group. Blood serum were analyzed for ALP levels on the 2nd, 8th and 14th days. Kinetic-IFCC method was used to find serum ALP levels. Data was analyzed using Mann-Whitney Test, paired T-test amd independence T-test. Scalded wound size was measured macroscopically over the course of 21 days to find contracture rate. In conclusion, Ashitaba extract is not proven to significantly reduce the serum ALP levels, increase contracture rate and enhance burn wound healing process. However, there was slight increase in contracture rate in treatment group as compared to control group. In addition, there was a lower ALP levels in treatment group as compared to control group in day 8.